Islamic Banking: Basic Concepts of Service Products and Their Implications in Society - Rosyidah, Tauwabur (ICO EDUSHA, 2024)
Islamic banking has emerged as an alternative option in the global financial system, offering products and services designed in accordance with Islamic sharia principles. This article aims to discuss in depth the basic concepts of Islamic banking products and services and their implications in society. Using a qualitative approach through literature study, this study explores several important aspects: first, the basic principles underlying Islamic banking, which include the prohibition of usury, gharar, and maysir. Second, the various types of products offered by Islamic banks, such as murabahah, mudharabah, and musyarakah financing, which are designed to meet customer needs in an ethical and equitable manner. This study also analyzes the socio-economic impact of Islamic banking in society. The results of the study indicate that Islamic banking not only functions as a tool to fulfill financial needs, but also contributes to strengthening social values, such as justice, cooperation, and social responsibility. Thus, Islamic banking can play a role in improving community welfare and encouraging inclusive economic growth. This study concludes that Islamic banking has the potential to become an important pillar in a fairer and more sustainable financial system, while inviting the public to understand and utilize Islamic financial products in everyday life.   Keywords: Sharia principles, Islamic economics, Social implications